The Influence of Interpersonal Communication, Work Environment, and Self-Efficacy on Employee Performance at Best Western Premier La Grande Hotel - Adilah Luthfi Sukmaputri; Deden Sutisna (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to obtain empirical evidence on "The Influence of Interpersonal Communication, Work Environment, and Self-Efficacy on Employee Performance at the Best Western Premier La Grande Hotel". The results of this study can be used as a contribution of thought for companies in an effort to improve employee performance through improving interpersonal communication, work environment, and self-efficacy. The research method used is descriptive and verification analysis. Data collection used is interviews using questionnaires accompanied by observation techniques, sampling techniques using saturated samples or censuses totaling 200 people. Data analysis techniques use multiple linear regression, multiple correlation, and the coefficient of determination partially or simultaneously. The results of the study show that simultaneously interpersonal communication, work environment, and self-efficacy have an influence of 55.1% on employee performance at the Best Western Premier La Grande Hotel. Partially, interpersonal communication has an influence of 23.5% on performance, and the work environment has an influence of 22.5% on employee performance. The more comfortable the work environment will improve employee performance at the Best Western Premier La Grande Hotel. Partially self self-efficacy has an influence of 8.8% on employee performance.